The extent of compliance and implementation of R.A. 6966 among academic librarians in Region III - Paez, Leonila S. (2000)
This study was aimed at determining: (1) the profile of the librarian-respondents in terms of sex, age, designation, years in service, eligibilities and their socio-economic status; (2) the educational training and status of the respondents; (3) the educational qualifications of the librarians as prescribed by the R.A. 6966; (4) the problems of non-licensed librarians toward compliance with R.A. 6966; and (5) the extent of complicance with, and implementation of R.A. 6966 among academic librarians of Region III. Data and relevant information were obtained by means of a set questionnaire utilizing Likert Scales and personal interviews. One hundred five (105) librarians in-charge of libraries of higher education institutions (HEIs) constituted the respondents of the study.